Development of the My Positive Health dialogue tool for children: a qualitative study on children's views of health. Issue 1 (13th April 2022) - de Jong-Witjes, Stacey; Kars, Marijke C; van Vliet, Marja; Huber, Machteld; van der Laan, Sabine E I; Gelens, Eva N; Berkelbach van der Sprenkel, Emma E; Nijhof, Sanne L; de Jonge, Maretha V; Rippen, Hester; van de Putte, Elise M
Abstract : Background: Children's views of health were explored in order to develop a health dialogue tool for children. Methods: A qualitative research design was used as part of a codesign process. Based on semi-structured interviews with both healthy children and children with a chronic condition (aged 8–18). Two approaches were applied. The first was an open exploration of children's views on health, which was then thematically analysed. Subsequently, a framework was used, based on the six-dimensional My Positive Health (MPH) dialogue tool for adults, to guide the second part of the interviews, focusing on reviewing the children's view on health within the context of the framework. For the final draft of the dialogue tool, a framework analysis was conducted and then validated by members of the 'children's council' of the Wilhelmina Children's Hospital. Results: We interviewed 65 children, 45 of whom had a chronic condition and 20 were healthy. The children described a broad concept of health with the central themes of 'feeling good about yourself' and 'being able to participate'. Based on the subsequent framework analysis, the wording of two of the six dimensions of the MPH dialogue tool was adjusted and the related aspects were adapted for better alignment with the children's concept of health. After these modifications, the tool fully matched the children's concept of health. Conclusion: The MPH dialogue tool for children was developed for children with and without a chronic condition, to help them open up about what they consider important for their health and well-being, and to improve directorship over decisions and actions that would affect their health. The MPH dialogue tool aims to support healthcare professionals in providing the type of care and treatment that is in line with the needs of their young patients/clients.